Perennials as Future Grain Crops: Opportunities and Challenges - Chapman, Elizabeth A.; Thomsen, Hanne Cecilie; Tulloch, Sophia; Correia, Pedro M. P.; Luo, Guangbin; Najafi, Javad; DeHaan, Lee R.; Crews, Timothy E.; Olsson, Lennart; Lundquist, Per-Olof; Westerbergh, Anna; Pedas, Pai Rosager; et al. (Frontiers in Plant Science, 2022)
Perennial grain crops could make a valuable addition to sustainable agriculture, potentially even as an alternative to their annual counterparts. The ability of perennials to grow year after year significantly reduces the number of agricultural inputs required, in terms of both planting and weed control, whilst reduced tillage improves soil health and on-farm biodiversity. Presently, perennial grain crops are not grown at large scale, mainly due to their early stages of domestication and current low yields. Narrowing the yield gap between perennial and annual grain crops will depend on characterizing differences in their life cycles, resource allocation, and reproductive strategies and understanding the trade-offs between annualism, perennialism, and yield. The genetic and biochemical pathways controlling plant growth, physiology, and senescence should be analyzed in perennial crop plants. This information could then be used to facilitate tailored genetic improvement in selected perennial grain crops to improve agronomic traits and enhance yield, whilst maintaining the benefits associated with perennialism.